DISKURSUS INTELEKTUAL DALAM FILSAFAT POLITIK NOAM CHOMSKY DAN RELEVANSINYA DI INDONESIA - Romanus Piter (Aggiornamento, 2022)
This research seeks to elaborate on intellectual discourse in Noam Chomsky's political philosophy. According to Chomsky, an intellectual can be a driving lever for societal change. This research aims to understand intellectual identity and responsibility in a democratic society. This research uses a qualitative method in the form of a critical perspective or approach and finds four important points. First, there are two intellectual identities according to Chomsky: moral value-oriented and technocratic. Second, people who are called intellectuals are people who have a sincere intention to elevate human nature: freedom, intelligence and creative power to create. Thus, intellectual status applies to all social statuses, both experts or experts in the academic world, practitioners, religious leaders, public officials, activists and the wider community. Third, the duties and responsibilities of an intellectual are to voice the truth and expose lies. Fourth, in Indonesia there are several intellectual challenges: the historical experience of intellectuals in the past being ostracized, sidelined and even killed has left its own horror for critical voices at this time; there are still intellectuals who neglect their responsibility to the wider community, both academics, activists, practitioners and even religious leaders; there are intellectuals who speak critically for justice and freedom, but their voices are ignored or even silenced. Indonesian intellectuals are called to educate society in all areas of life such as social, economic, political, cultural, educational, religious, environmental and media